Cauterization's history in the Persian medicine school. Issue 1 (2nd January 2023) - Khosravi, Azam; Van Hee, Robrecht; Asadi, Mohammad Hossein; Changizi-Ashtiyani, Saeed; Amini, Saeed
Abstract: Background: Cauterization has been used in various medical schools to prevent and treat diseases. Its application dates back to shortly after the invention of fire. Despite its long history, different aspects and the importance of cauterization in various medical schools have remained elusive. The present study addressed the milestones and progress of cauterization from ancient times to the present, emphasizing the innovations of the Persian medicine school. Methods: The present study is based on searching in the library documents of famous Persian medicine scholars and data from databases such as Ovid, PubMed, Science Direct, Scopus, ProQuest, and Google Scholar search engines. Results: Persian Medicine scholars used various cauterization methods such as hot metals and corrosive drugs to stop bleeding, prevent the development and spread of infection, and treat hydrocephalus and rabies. Cauterization has been associated with considerations to prevent irreversible tissue damage and whether or not it is internal or external. Conclusion: Cauterization has been associated with different practical purposes. With evolutionary progress and the use of different techniques and tools throughout history, the tools such as Electrocautery or Galvanocautery are some manifestations of new applications of cauterization. Numerous studies have indicated the continuation of newer applications, indicating the inexhaustible human interest in this ancient technique.